Kamu hastanelerinde özerkleşmesi sürecinde profesyonel sağlık yöneticisi ihtiyacının belirlenmesi Trabzon iline ait bir çalışma - Köse, Aslı (My University, 2008)
1.ÖZET Sağlık sektöründeki reform çalışmaları başlığı altında sağlık sisteminde iyileştirme yapmayı amaçlayan projeler gündemde bulunmaktadır. Bu çalışmalardan şu an için gündemde olan sağlıkta dönüşüm programının bir bileşeni de kamu hastanelerinin özerkleştirilmesidir. Sağlık Bakanlığı’na bağlı hastanelerin verimliliğini arttırmak için hastanelerin idari ve mali açıdan özerk kurumlar haline getirilmesi planlanmaktadır. nde sağlıkta dönüşüm kamu hastanelerinin özerkleştirilmesi süreci, Dünya’da ve Türkiye’de sağlık yönetimi eğitimi, profesyonelleşme ve de en son olarak Türkiye’de mevcut duruma değinilmiştir. Altıncı bölümde ise veri toplama aracı olarak elde edilen bulgular sunulmuş ve bu bulgular ışığında değerlendirilmeler yapılmıştır. Araştırma, kamu hastanelerinin özerkleştirilmesi sürecinde yaşanacak profesyonel sağlık yöneticiliği yöneticilere olan ihtiyacı belirlemek amacı ile Trabzon ilinde hizmet veren toplam 15 kamu hastanesinde çalışan toplam 130 üst düzey yönetici ile anket yöntemi uygulanarak yapılmıştır. Üst düzey yönetici hastanede çalışan Başhekim, Başhekim Yardımcısı, Başhemşire, Başhemşire Yardımcısı, Hastane Müdürü, Hastane Müdür Yardımcısı olarak tanımlanmıştır. Bulgular, sağlık sektöründe yanlış yönetim kaynaklı sorunların çözümlenebilmesi ve gerçekleşecek reform çalışmalarının başarıya ulaşabilmesi için profesyonel sağlık yöneticiliği eğitimi almış yöneticilerin süreç içerisinde yer alması gerekliliğini göstermiştir. Anahtar Sözcükler: Özerkleştirme, Profesyonel, Sağlık Yönetimi, Sağlık Yönetimi Eğitimi, Yönetici. 1.

Determining The Need For Professional Managers In The Progress Of Autonomization Of Public Hospitals – A Study In The Province Of Trabzon Projects with the purpose of improving the health system under the title of Reform Works In Health Sector are on the agenda. One element of the transformation programs in health that are currently on the agenda is the autonomization of the public hospitals. It is planned that the hospitals bound to the Ministry of Health will be administratively and financially autonomized in order to increase the productivity. Transformation programs in health, the autonomization process of the public hospitals, health management training in the world and Turkey, professionalization as well as the present situation in Turkey have been referred to in the section general information. In the sixth section, the findings obtained as data collection means have been submitted and assessments were made depending on these findings. The study was carried out in form of an inquiry that was made with 130 top-level managers in total who are employed in totally 15 public hospitals serving in the City of Trabzon with the purpose of determining the necessity for professional health administration managers to be experienced during the process of autonomization of public hospitals. Chief Physicians, Assistant Chief Physicians, Chief Nurses, Assistant Chief Nurses, Hospital Director, Hospital Vice-Directors who are employed in the hospitals have been defined as top-level managers. The findings have shown that administratives who have obtained professional health administrator training must take place in the process in order to solve the problems arising from false management in the health sector and to achieve success in the reform works to be realized. Key Words: Autonomization, Health Management, Health Management Training, Manager, Professional.
Keywords: Hastaneler; Sağlık Kurumları Yöneticiliği